RIVAROXABAN OF THE BAYER COMPANY SIGNIFICANTLY (BY 24%) REDUCES THE RISK OF STROKE, CARDIOVASCULAR DEATH AND MYOCARDIAL INFARCTION IN PATIENTS WITH CHRONIC ISCHEMIC HEART DISEASE OR PERIPHERAL ARTERIAL DISEASE - статья Редакционная (Столичная издательская компания, 2017)
Press release of JSC "BAYER"